2014
DOI: 10.15740/has/ajbs/9.2/151-155
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Metarhizium anisopliae, Beauveria bassiana and neem oil against tomato fruit borer, Helicoverpa armigera under field condition

Abstract: A field study was conducted at farmers field of Jorhat, Assam during 2010-11 to evaluate the efficacy of three commercial biopesticides, two based on insect pathogenic fungi viz., Beauveria bassiana and Metarhizium anisopliae and one botanical-Neem oil in comparison with chemical-cypermethrin against the tomato fruit borer (Helicoverpa armigera). The study revealed the reduction in fruit damage was upto 92.20 per cent in cypermethrin treated plot followed by 91.12 per cent, 88.74 per cent and 87.01 per cent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, the use of bio-pesticides like M. anisopliae and B. bassiana in treatment modules has shown commendable performance in reducing shoot infestation due to L. orbonalis. This aligns with findings reported by Nayak et al (2013) and Phukon et al (2014) and showcasing the effectiveness of M. anisopliae and B. bassiana against brinjal shoot and fruit borer.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the use of bio-pesticides like M. anisopliae and B. bassiana in treatment modules has shown commendable performance in reducing shoot infestation due to L. orbonalis. This aligns with findings reported by Nayak et al (2013) and Phukon et al (2014) and showcasing the effectiveness of M. anisopliae and B. bassiana against brinjal shoot and fruit borer.…”
Section: Discussionsupporting
confidence: 93%
“…Spinosad 48 SC was found to be the most effective insecticide for the control of H. armigera, followed closely by indoxacarb15 EC. Phukon et al, (2014) revealed the reduction in fruit damage was up to 92.20 per cent in cypermethrin treated plot followed by 91.12 per cent, 88.74 per cent and 87.01 per cent in the plots treated with Neem oil, B. Bassiana and M. Anisopliae, respectively due to H. armigera larvae over control. The highest increase in yield over control was noticed in cypermethrin treated plots (62.85%) followed by neem oil treated plots (41.83%).…”
Section: Th Day After II Nd Sprayingmentioning
confidence: 94%
“…Researchers proved that neem (oil) is as effective as cypermethrin in controlling the tomato fruit borer, Helicoverpa armigera (Hb.) on tomato (Phukon et al 2014). Neem products can be readily combined with many other bioagents including microbes (Mohan et al 2007).…”
Section: Main Textmentioning
confidence: 99%